Reduced anogenital distance, hematuria and left renal hypoplasia in a patient with 13q33.1-34 deletion: case report and literature review - Xue He; Huijun Shen; Haidong Fu; Chunyue Feng; Zhixia Liu; Yanyan Jin; Jianhua Mao (BMC, 2020)
Abstract Background 13q33-q34 microdeletions are rare chromosomal aberrations associated with a high risk of developmental disability, facial dysmorphism, cardiac defects and other malformation of organs. It is necessary to collect and report evidence of this rare chromosome mutation to improve the prognosis of this rare disease. Case presentation We report a patient harboring an 11.56 Mb microdeletion at 13q33.1-34 region, which contains about 30 OMIM genes. Besides the common clinical manifestations such as facial dysmorphism, developmental delay, intellectual disability, epilepsy, and congenital heart disease, she also suffered from a reduced anogenital distance, hematuria and left renal hypoplasia. Most related cases were characterized by facial deformity and heart defects, but there were few reports on renal malformation, especially regarding renal hypoplasia with hematuria. Conclusion We have reported a patient suffering from a reduced anogenital distance, hematuria and left renal hypoplasia. A de novo 11.56 Mb deletion ranging from 13q33.1 to 13q34 (Chr13:103542220-115,106,996) was found by SNP-array analysis. It might be the first time for hematuria and renal hypoplasia to be reported as symptoms of 13q33-q34 deletion syndrome Neurodevelopmental disability, heart defects and urogenital/anorectal anomalies may be resulted from common or overlapping regions of deletion in chromosome bands 13q33.1-q34 and may share a common molecular mechanism.